Effects of iron and chromium on the dynamic properties of oxygen in liquid lead–bismuth eutectic alloy. (April 2017) - Xu, Yichun; Zhang, Yange; Li, Xiangyan; Liu, Wei; Li, Dongdong; Liu, C.S.; Pan, B.C.; Wang, Zhiguang
Abstract : Highlights: Diffusivities of oxygen, Fe and Cr at different temperatures were obtained for deriving the relationships between diffusivities and temperatures. Oxygen atoms could be strongly attracted towards Fe and Cr atoms, forming metal oxide complexes dominated by Fe3 O4 and Cr2 O3 . These oxide complexes retard oxygen diffusion and reduce the concentration of free oxygen in LBE. Abstract: Ab initio molecular dynamics simulations were performed to investigate the effects of iron (Fe) and chromium (Cr) on the dynamic behaviour of oxygen in liquid lead–bismuth eutectic (LBE). The results indicated that oxygen atoms could be strongly attracted towards Fe and Cr atoms, forming metal oxide complexes dominated by Fe3 O4 and Cr2 O3 . These oxide complexes could retard oxygen diffusion and reduce the concentration of free oxygen in LBE, thereby leading to an increase in the output of oxygen sensor in experiments. Besides, the diffusivities of Fe and Cr in LBE were obtained at different temperatures.